Pengaruh Income Expectation, Entrepreneurial Knowledge, dan Digital Competencies terhadap Entrepreneurial Intention Gen Z - Eka Nurul Hidayah; Corry Yohana; Rizka Zakiah (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to identify and analyses the influence of income expectations, entrepreneurial knowledge, and digital competencies on entrepreneurial intention among Generation Z. This study employs a quantitative approach with a cross-sectional survey design. The study population consists of Generation Z individuals aged 14–29 residing in DKI Jakarta, with an unknown population size. Sampling was conducted using non-probability sampling via purposive sampling, resulting in 170 respondents who met the study criteria. Data were collected via an online questionnaire using a six-point Likert scale distributed through Google Forms, then analyses using IBM SPSS Statistics version 25 software, reliability tests, classical assumption tests, multiple linear regression analysis, partial tests (t-tests), and coefficient of determination tests. The results indicate that Income Expectation, Entrepreneurial Knowledge, and Digital Competencies each have a positive and significant effect on Entrepreneurial Intention, both partially and simultaneously, with a combined explanatory power of 37.6%. Among these three variables, Income Expectation contributes the most to entrepreneurial intention. These findings indicate that the expectation of earning a decent income is the most dominant consideration for Generation Z in forming entrepreneurial intention, while entrepreneurial knowledge and digital competencies serve as supporting cognitive and technical tools for capitalizing on business opportunities in the digital age.